On Gadamer's Heteronomy Argument: The "Irruption" of Reality vs. its "Strategic Excision" - Bech, Josep Maria (Labyrinth, 2022)
The aim of this paper is to find out whether Gadamer is entitled to hold together his finitist commitment to the heteronomy of art and thought, and his advocacy of an "endless conversation with itself" of humankind. We focus on three texts: Gadamer’s dismissal of Carl Schmitt’s outside-in account of the heteronomy implied by the "irruption of reality" in the play Hamlet and, as Archimedean point, Shakespeare’s "excision of reality" according to Stephen Greenblatt, and its inside-out heteronomic consequences. The results: Schmitt’s approach restricts Gadamer’s argument on the "endless dialogue", Gadamer’s rejoinder aggravates his own argumentative fragility, and Greenblatt’s perspectivation discloses a non-sequitur. The inspection of these texts attests that heteronomy per se does not entail any openness to "creative" interpretations, that a universalized logos endiéthetos is a chimera, and that there cannot be any "infinite conversation" which would sustain the Gadamerian interplay of question and answer.